ANALYSIS THERMAL OF THERMOPLASTIC ELASTOMER WITH FILLER POWDER WASTE TIRE - Eva Marlina Ginting; Nurdin Bukit; Khairina Fitri; Erna Frida (AGRIUM: Jurnal Ilmu Pertanian, 2016)
This study aims to determine the thermal properties of the thermoplastic elastomer with filler powders waste tires on the mixing of the rubber SIR-20 and polyethylene by using of Differential Thermal Analysis (DTA) and Termogravimetrik Analysis (TGA). The process of sample preparation is done in Internal Mixer with mixing polyethylene, rubber SIR-20, compatibilizer Polyethylene Maleic Anhydride (PEMA), sulfur and powder scrap tires 80 mesh with varying from (0, 10, 20, 30) phr, with a temperature of 180 ° C and rotor speed of 60 rpm for 15 minutes. DTA analysis results obtained by the temperature of the melting point and the highest reduction in heat flow without powder obtained in composition of scrap tires with a temperature that is equal to 160.3 0C microV -11.975. While the TGA test results obtained the highest mass reduction obtained on the composition without powder used tires is 18.59 mg or by 58 792% with a temperature of 502.6 0C.Keywords: powder waste tires, natural rubber, TGA, DTA